(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
The objective of this article is to present the experience of an extension project called Artistic Intervention in the Costanera Centro-Posadas Linear Park that depends on the Faculty of Humanities and Social Sciences of the National University of Misiones. This project sought, based on musical interventions, to increase the emotional value of tourist visits in Provincial Parks, the new spaces chosen post-pandemic. Although the general objective of the project is fulfilled, other triggers external to it are analyzed and that are typical of any link between the different actors that make up the project itself. Through field records (Guber, 2004), written and photographic, after the visits as a methodological tool, we recover the observed and verbalized experiences, in order to present the peculiarities that the project adopted for all the people involved.